Clinical Practice Guidelines for the Detection and Treatment of Amblyopia: A Systematic Literature Review. Issue 2 (3rd April 2022) - Lingham, Gareth; McGuinness, Myra B.; Safi, Sare; Gordon, Iris; Evans, Jennifer R.; Keel, Stuart
ABSTRACT: Purpose: The World Health Organization's Package of Eye Care Interventions (PECI) aims to support incorporation of amblyopia detection and treatment into health service provision. The aim of this study was to systematically review clinical practice guidelines (CPGs) for amblyopia to inform the development of this package. Methods: MEDLINE, Embase, CINAHL and Global Index Medicus databases, guideline databases and professional body websites were searched for CPGs published in English between 2010 and 9th March 2020. Guidelines were assessed using the AGREE II tool. Results: Five CPGs from North America published between 2017–2019 were identified. One CPG provided recommendations on amblyopia treatment and four focused on amblyopia detection and assessment. Non-specialist screening for amblyopic risk factors was recommended in children aged 3–5 years. At least one comprehensive eye examination was recommended for infants and children aged 0–5 years. Treatment recommendations consisted of refractive correction followed by occlusion or cycloplegic penalization. Conclusions: Additional evidence is required to compare the benefits and limitations of comprehensive eye examinations for asymptomatic children to those from screening programs. Identified CPGs were produced in high-resource countries and may not be readily applied in lower resource settings where the PECI has the greatest potential to improve service provision.